An evaluation of tourism activities in Turkey with reference to sustainable regional development - Ferhan Gezici; Gunduz Atalik (European Regional Science Association (ERSA), 1998)
As tourism becomes one of the most significant tools in regional development processes in developing areas, increasing interest turns toward the impact of tourism on environmental concerns. The changing processes and the results of many researches show if natural, historical and cultural environment could not be protected, there would be no expectations for sustainability in tourist destination areas. In this way, relevant policies on sustainable regional development appear to keep an optimality between development and environment when maximization policies for value added rates in tourism activities take priority for development plans in this respect. The main objective in this paper will be to analyse the impact of tourism activities in Turkey in the framework of some case studies on special areas which are involved in the international cultural heritage. It is supposed that intensity of problems changes related to type of tourism and characteristics of the region. In this way, some analytical methods and techniques, e.g. semantic differential testing, factor analysis and cross-table will be used in order to evaluate the contribution of tourism activities on some sample areas in sustainable regional development in Turkey as a Mediterranean country.
Keywords: 330